Sacubitril/Valsartan partially alleviates myocardial infarction injury by activating the FGF21 signaling pathway via PPARs - Wenjuan Wei; Guangsen Xu; Jiaer Gao; Guiyun Wang; Ye Wang; Caiyan Li; Junwei Zheng; Huiying Lu; Yunyan Lu; Kun Wang; Hongtao Xu; Cong Wang; et al. (Cardiovascular Diabetology)
Abstract The recent discovery of clinically significant data, alongside novel physiological and pathological occurrences surrounding sacubitril/valsartan (Sac/Val) beyond its approved indications, necessitates an urgent reevaluation of its underlying mechanism of action. In the present investigation, we observed a substantial elevation in the serum levels of fibroblast growth factor 21 (FGF21) among patients with acute myocardial infarction (AMI) who were administered Sac/Val, compared to those who were not, utilizing ELISA-based measurements. Furthermore, through the utilization of a mouse model of myocardial infarction induced by ligation of the left anterior descending branch, we confirmed that FGF21 mediates the cardioprotective effect of Sac/Val, employing both loss-of-function and gain-of-function approaches. Molecular docking and SPR experiments validated that Sac/Val can regulate FGF21 via its interaction with PPARs, and verified the role of PPARs in mediating Sac/Val regulation of FGF21 by inhibiting PPARs. In conclusion, we found that Sac/Val can act as an agonist of FGF21, which provides a new idea for the development of FGF21 drugs, and FGF21 as a new target of Sac/Val to ameliorate myocardial infarction, which provides a basis for new indications for Sac/Val.